Judicial Review of the Application of Ultra Vires Doctrine in Malaysia and Indonesia: A Legal Comparison - Zilmi Haridhi; Elsa Daniella Simbolon; Naomi Audri Klarisa Sitompul; Akmal Pauzi; Chairil Ikhwan (Recht Studiosum Law Review, 2024)
The Ultra Vires Doctrine serves as a fundamental principle in corporate law, delineating the boundaries of governmental authority and ensuring adherence to legal framework. This comparative study explores the application of the Ultra Vires Doctrine in the judicial systems of Malaysia and Indonesia. Through an analysis of relevant case law, statutory provisions, and scholarly literature, the study highlights similarities and differences in the interpretation and implementation of the doctrine across these jurisdictions. While both countries recognize the importance of restraining government action within legal limits, variations emerge in the extent to which courts intervene and the factors considered in determining ultra vires acts. By shedding light on these legal frameworks, this research contributes to a deeper understanding of corporate law principles in Malaysia and Indonesia and provides insights for legal practitioners, policymakers, and scholars seeking to navigate and strengthen the rule of law.